Management of Education Financing According to the Qur’an and Hadith - Winarto, Andri; Mahmud, Muchammad Eka; Muadin, Akhmad (Edumaspul: Jurnal Pendidikan, 2023)
This study aims to determine how the management of education financing according to the Qur’an and Hadith. The research method used is a literature review method sourced from previous studies published in journals, then analyzed and reformulated how to manage education financing according to the Qur’an and Hadith. Based on the results of the analysis, it is known that 1) The input of education financing management from the perspective of the Quran and Hadith is Rabani, namely the management of education financing whose concepts, principles and foundations are taken and concluded from the Quran, which is a holy book for all humans, especially Muslims, which Allah Almighty revealed to the Prophet Muhammad SAW; 2) Output, namely a) management of educational financing perspective of the Quran and Hadith is Ubudiah (mahdhoh worship and ghoiru mahdhoh worship); b) akhlaki, which is having morals (ethics) or being moral. In managing and managing education costs, in addition to being aimed at the success of activities and programs, morals are also needed in its management so as not to cause damage and loss. The akhlaki management of education financing in the Qur’an and Hadith is redacted with the word "la tabkhosū or la tukhsiru."